Role of bone morphogenetic proteins in form-deprivation myopia sclera - Wang, Qing (Molecular Vision, 2011)
PURPOSE: To clarify the role of bone morphogenetic proteins (BMP-2,-4,-5) in sclera remodeling during myopia induction and their effect on sclera fibroblasts in cell culture. METHODS: Reverse transcription and polymerase chain reaction (RT–PCR) as well as immunofluorescence were used to detect the expression of the BMPs in human and guinea pig posterior sclera. In guinea pig form-deprivation myopia (FDM) model, RT–PCR and western blotting were used to investigate changes of BMP expression in the posterior sclera. Human sclera fibroblast (HSF) was primarlly cultured and treated with various doses of BMP-2. Cell proliferation was evaluated by the MTT assay. RT–PCR and western-blot were used to determine the changes of collagen I, aggrecan, and possible activated signal pathway. Cell phenotype and activated signal pathway, especially for α-smooth muscle actin (α-SMA) and phospho-smad1/5/8 were then further investigated by cytoimmunofluorescence staining. RESULTS: Both human and guinea pig sclera express BMP-2, −4, and −5. In FDM eyes, BMP-2 and BMP-5 expression were reduced in the posterior sclera. Cell proliferation increased significantly (p<0.05) and more cells differentiated into myofibroblast when incubated with 100 ng/ml BMP-2 . The expressions of collangen I, aggrecan, and phospho-smad1/5/8 significantly increased (p<0.05 respectively) as well. CONCLUSIONS: Various BMPs were expressed in human and guinea pig sclera. In the posterior sclera, the expressions of BMP-2 and BMP-5 decreased in FDM eyes. BMP-2 might be able to promote HSF proliferation and differentiation, as well as to help extracellular matrix synthesis potentially through classical Smad pathway.